ANALYSIS OF US-NATO ENTANGLEMENT IN RUSSO-UKRAINIAN CONFLICT: 'WESTERN AXIS' AN EFFORT TO CONTAIN CHINA IN EUROPE - Maulidina, Syifa; Saputra, Oddie Bagus (UI Scholars Hub, 2023)
The Ukraine-Russia conflict is a complex one. Some countries intend to defend national interests regarding border areas, energy sources, and international trade routes such as the United States, NATO, and China. The United States-NATO is trying to maintain the status quo over the Euro-Arctic region. Meanwhile, China took advantage of this conflict to expand into the European market. In addition, China has also benefited in the military sector to modernize its military arsenal and cheap energy sources amid the global energy crisis from Russia. Therefore, to help the process of analyzing the issue, this study uses the concept of balancing to see how the US-NATO shapes the perception of threats to China. Henceforth, both know what form of deterrence and containment strategy to employ in their involvement in the Ukraine-Russian conflict, especially to stem China's expansion in the Caucasus and Arctic regions.